The Diagnostic Value of Contrast‐Enhanced Ultrasound for Localization of Parathyroid Lesions in Primary Hyperparathyroidism: Comparison With Color Doppler Ultrasound. (31st March 2022) - Piccin, Ottavio; D'Alessio, Pasquale; Serra, Carla; Felicani, Cristina; Vicennati, Valentina; Repaci, Andrea; Pagotto, Uberto; Cavicchi, Ottavio
Abstract : Objectives: Preoperative localization of pathological parathyroid glands with imaging is essential for focused unilateral neck exploration and minimally invasive techniques. Recently published studies suggested that contrast‐enhanced ultrasonography (CEUS) had high accuracy in the localization of hyperfunctioning parathyroid glands, with a general increase in the sensitivity as compared to conventional sonography. The purpose of this study was to determine the usefulness of CEUS in the localization of parathyroid lesions relating to surgical and histopathological data, in comparison to color Doppler ultrasound (CDUS), in the same series of patients. Methods: Records of 142 patients who underwent parathyroidectomy were retrospectively examined comparing imaging and intraoperative/histopathologic findings. Results: The overall sensitivity of CEUS was 77.6% compared with 74.6% for CDUS, although no significative differences were found ( P = .516). Conversely, CDUS has shown higher sensitivity than CEUS in the group of patients with associated thyroid pathology but there was no statistical difference ( P = .529). The sensitivity for detection of multiple adenomas was the same for both procedures. Conclusions: We found no significative superior sensitivity of CEUS also in case of concomitant thyroid pathology and multiple glands disease.